Neuromodulation in response to electroconvulsive therapy in schizophrenia and major depression - Thomann, Philipp; Nolte, Henrike Maria; Hirjak, Dusan; Hofer, Stefan; Seidl, Ulrich; Depping, Malte S.; Maier-Hein, Klaus H. (Brain stimulation, 2017)
Background: Electroconvulsive therapy (ECT) is one of the most effective treatments in severe and treatment- resistant major depressive disorder (MDD). ECT has been also shown to be effective in schizophrenia (SZ), particularly when rapid symptom reduction is needed or in cases of resistance to drug-treatment. However, its precise mechanisms of action remain largely unknown. Objective/Hypothesis: This study examined whether ECT exerts disorder-specific or unspecific modulation of brain structure and function in SZ and MDD. Methods: We investigated neuromodulatory effects of right-sided unilateral ECT in pharmacoresistant patients with SZ or MDD. Magnetic resonance imaging was conducted before and after ECT to investigate treatment- related effects on brain structure and function. Imaging data were analyzed by means of Voxel Based Morphometry and Resting State Functional Connectivity (RSFC) methods. Results: Right unilateral ECT induced transdiagnostic regional increases of limbic gray matter and modulations of neural coupling at rest. Structural effects were accompanied by a decrease in RSFC within temporoparietal, prefrontal and cortical midline structures, and an increase in hypothalamic RSFC. The extent of structural and functional change was partially inversely associated with the baseline measures. Conclusion: The present findings provide first evidence for transdiagnostic changes of brain structure together with modulation of brain function after ECT. The data indicate diagnosis-unspecific mechanisms of action with respect to regional gray matter volume and resting-state functional connectivity.
Gesehen am 26.04.2018